Use of benthic foraminifera with elongated tests (endofauna) in the determination of depositional environments: case of the interval 1840-345 m of oil-well IVCO 25 off Côte d"Ivoire, West Africa - Digbehi, Zéli Bruno; Affian, Kouadio; Kouamé, Aka; N. da, Loukou Victor; Tahe, Thierry (Anuário do Instituto de Geociências, 2006)
Abstract